ANALISIS HUKUM MENGENAI PENCABUTAN HAK POLITIK BAGI KORUPTOR BERDASARKAN SUDUT PANDANG HAK ASASI MANUSIA - Sabungan Sibarani (Prosiding Seminar Nasional Pakar, 2019)
Revocation of political rights for convicted corruption cases in the perspective of human rights, where political rights are part of human rights, therefore if there is revocation of political rights which are part of an additional criminal application, there must be a limitation on the revocation of rights. The application of additional penalties in the form of revoking the right to vote and be elected (political rights) insofar as it is not permanent does not violate human rights. Limitation or limitation began to take effect, or in other words began to be counted on the convicts who served an additional sentence revoked political rights. The right to hold office, the right to vote and be elected Article 35 of the Criminal Code, also overlaps with the decision of the Constitutional Court (Constitutional Court). Article 38 of the Criminal Code determines "revocation of rights shall take effect on the day the court decision begins to be carried out." While the Constitutional Court decision No. 4/PUUVII/2009 has determined that the penalty for revocation of political rights is considered constitutional with the limitation of rights only up to five years after the convict has finished carrying out his sentence.